Summertime distributions of peroxyacetyl nitrate (PAN) and peroxypropionyl nitrate (PPN) in Beijing: Understanding the sources and major sink of PAN. (February 2015) - Zhang, Gen; Mu, Yujing; Zhou, Lingxi; Zhang, Chenglong; Zhang, Yuanyuan; Liu, Junfeng; Fang, Shuangxi; Yao, Bo
Abstract: Peroxyacetyl nitrate (PAN), a major secondary pollutant in the atmosphere, has received much concern for its particular importance in atmospheric chemistry and adverse effects on human and plants. Atmospheric PAN and PPN were measured by using a gas chromatograph equipped with electron capture detector (GC-ECD) from June to September 2010, and the source and major sink for PAN were firstly studied in Beijing. The distinct diurnal variations of PAN and PPN with maximum in the afternoon were observed, and the mean and maximum values were 2.61 ± 2.57 ppbv (N = 839) and 12.5 ppbv for PAN and 0.52 ± 0.38 ppbv (N = 152) and 2.16 ppbv for PPN during the measuring period, respectively. Good correlation (R = 0.85) between PAN and PPN with a slope (ΔPPN/ΔPAN) of 0.134 indicated that anthropogenic volatile organic compounds (AVOCs) dominated the photochemical formation of PANs in Beijing. Further, we found acetaldehyde was the predominant carbonyl precursor of PAN with the contribution of 59.7% to the total peroxyacetyl (PA) radical. Methyl glyoxal, methacrolein, acetone, methyl vinyl ketone, and biacetyl contributed 7.1%, 8.8%, 19.7%, 3.4%, and 1.3% to total PA radical, respectively. Anti-correlation between PAN concentrations and the NO/NO2 ratios was found during the whole investigating period. In addition, the amount of PAN lost by thermal decomposition (TPAN) accounted for remarkable fractions of PAN observed under high temperature during both daytime and nighttime. Graphical abstract: Highlights: Atmospheric PANs were measured by using GC-ECD during summertime in Beijing. High pollution levels of PAN and PPN were found. Acetaldehyde was the predominant precursor of PAN in the investigating period. Thermal decomposition of PAN played an important role in its chemical process.